2021
DOI: 10.1186/s12944-021-01468-y
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm shift: the primary function of the “Adiponectin Receptors” is to regulate cell membrane composition

Abstract: The ADIPOR1 and ADIPOR2 proteins (ADIPORs) are generally considered as adiponectin receptors with anti-diabetic properties. However, studies on the yeast and C. elegans homologs of the mammalian ADIPORs, and of the ADIPORs themselves in various mammalian cell models, support an updated/different view. Based on findings in these experimental models, the ADIPORs are now emerging as evolutionarily conserved regulators of membrane homeostasis that do not require adiponectin to act as membrane fluidity sensors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 126 publications
(148 reference statements)
1
34
0
Order By: Relevance
“…Similarities were also iden-tified in Caenorhabditis elegans, where two AdipoRs homologs exist, and their disruption leads to membrane rigidification as a result of the accumulation of saturated fatty acids in plasma membranes [41]. This suggests that AdipoRs have an enzymatic activity that is independent of adiponectin, since C. elegans lacks adiponectin homolog [42]. Indeed, studies utilizing human cell lines showed that depletion of AdipoRs resulted in a higher accumulation of saturated fatty acids (SFAs) in plasma membranes, resulting in their rigidification [43].…”
Section: Adiponectin Receptors 1 and 2 In Regulation Of Metabolism And Membrane Homeostasismentioning
confidence: 76%
See 2 more Smart Citations
“…Similarities were also iden-tified in Caenorhabditis elegans, where two AdipoRs homologs exist, and their disruption leads to membrane rigidification as a result of the accumulation of saturated fatty acids in plasma membranes [41]. This suggests that AdipoRs have an enzymatic activity that is independent of adiponectin, since C. elegans lacks adiponectin homolog [42]. Indeed, studies utilizing human cell lines showed that depletion of AdipoRs resulted in a higher accumulation of saturated fatty acids (SFAs) in plasma membranes, resulting in their rigidification [43].…”
Section: Adiponectin Receptors 1 and 2 In Regulation Of Metabolism And Membrane Homeostasismentioning
confidence: 76%
“…In addition, upon palmitate treatment, cells showed mitochondrial respiratory defects and poor viability [44]. Intriguingly, supplementation with mono-or polyunsaturated fatty acids, which are known to increase membrane fluidity, was able to revoke detrimental effects of AdipoR2 silencing [42,44]. These findings suggest that the primary function of AdipoRs may not be adiponectin binding but the regulation of membrane homeostasis.…”
Section: Adiponectin Receptors 1 and 2 In Regulation Of Metabolism And Membrane Homeostasismentioning
confidence: 98%
See 1 more Smart Citation
“…AdipoR1 and AdipoR2 are members of the PAQR (Progestin and AdipoQ Receptors) protein family that are emerging as regulators of fatty acid desaturation and membrane homeostasis [ 12 ]. These proteins have seven transmembrane domains with a cytosolic N-terminus and their C-terminus pointing towards the extracellular space [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These proteins have seven transmembrane domains with a cytosolic N-terminus and their C-terminus pointing towards the extracellular space [ 13 ]. The AdipoRs were initially identified as adiponectin receptors [ 14 ], but recent experimental evidence based on studying the yeast [ 15 – 19 ] and C. elegans [ 20 – 28 ] homologs, and the AdipoRs themselves [ 23 – 27 , 29 , 30 ], suggests that their primary cellular function is in membrane homeostasis and is independent of adiponectin (reviewed in [ 12 ]). In particular, the AdipoRs react to membrane rigidification, e.g.…”
Section: Introductionmentioning
confidence: 99%